Struggle for Substantive Justice and Community Development: Transgender Subjects in Contemporary India - Kumar, Pushpesh (ASEAN Journal of Community Engagement, 2021)
This paper discusses the transgender community's fight for justice and developmental rights since 2014 and the response of the Indian Government toward this assertion. The point of choosing 2014 as the starting point is not because the fight for their justice actually begins in this year but because India witnessed an intensification and an increase in public visibility of transgenders’ mobilization following the recognition of members of transgender communities as legal citizens through the landmark Indian Supreme Court (Court) verdict called the National Legal Services Authority Union of India (NALSA). In documenting transgenders’ mobilization and the state's response, the author has substantially relied on secondary sources—newspaper articles and pieces in magazines, blogs, and other online community networks. The narratives of a few transgender activists and intellectuals reaffirm the critiques offered through the media and online community blogs and networks. It gives one the impression of a neoliberal state, which, while willing to protect the constitutional rights of many marginalized groups, finds it hard to fulfill promises that might require the allocation of substantial fiscal and monetary resources. The consistent collective mobilizations of the transgender communities, however, resulted in some concrete gains and developmental rights.